A study on the effects of quality, price, environmental value and perceived behaviour control towards intension to accept electricity demand side programs; A case study of Qatar kahramaa - Al-Ghalebi S.A.M.; Sharif Z.M.; Al-Shameri A.S.A.S.; Saif S.S.A.; Al Aamri S.I.M. (IBIMA Publishing, 2023)
A prevalent problematic issue spreading nowadays among the global community is the increasing demand of electricity, and Demand Side Management programs are suggested to be the best method for reducing the demand of electricity. Nevertheless, implementing such technologies is still an issue because the behavior of customers is different from one region to another, and the applicability of such technologies largely depends on the perceptions and the acceptance level of that specific region. Therefore, the current quantitative study was conducted to investigate the variables that affect the intention to accept the demand side management programs among the KAHRAMAA employees in Qatar; namely, attitude, quality value, price value, environment value and the perceived behavior control. The sample size of this study consisted of 294 questionnaires. The study used SPSS 22.0 for analyzing the results. The findings revealed that all the factors were having high mean values. The study also highlighted three main factors which do have an impact on the intention to accept demand side management programs which are quality value, environment value, and perceived behavior control. Besides, some recommendations have been provided for the future research and policy makers. Copyright 2021. Samar Abdulrazzaq Mohammed AL-GHALEBI, Zainon Mat SHARIF, Ahmed Saleh Ahmed Saif AL-SHAMERI, Saba'a Saleh Ahmed SAIF and Saleh Ibrahim Mohammed AL AAMRI. Distributed under Creative Commons Attribution 4.0 International CC-BY 4.0